2015
DOI: 10.1186/s12890-015-0019-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of intrathoracic Castleman disease: a retrospective analysis of 48 cases in a single Chinese hospital

Abstract: BackgroundThorax is the common place to develop Castleman disease (CD), but there is no systemic clinical analysis for intrathoracic CD.MethodsWe conducted a retrospective analysis of 48 intrathoracic CD patients with definite pathological diagnosis who were hospitalized between 1992 and 2012 in a Chinese tertiary referral hospital.ResultsThe study included 16 cases with unicentric CD (UCD) and 32 cases with multicentric CD (MCD). UCD were younger than MCD (30.5y vs 41.6ys, P < 0.05). MCD were more symptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 43 publications
(90 reference statements)
3
36
1
4
Order By: Relevance
“…But this ratio is much lower than the ratio reported in HIV-positive patients (Table 2). On the contrary, a study from China found female preponderance in CD [8]. The reasons for lower male to female ratio in our study and female predominance in a study from China remain unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…But this ratio is much lower than the ratio reported in HIV-positive patients (Table 2). On the contrary, a study from China found female preponderance in CD [8]. The reasons for lower male to female ratio in our study and female predominance in a study from China remain unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, many of the HIV positive patients die of other complications before developing uncommon neoplasm-like CD, and this phenomenon can create an impression that CD is uncommon in Asian patients suffering from HIV. Our series and the data from China [8] also reflect the same as none of the patients with CD reported in these studies was positive for HIV. A pertinent question can arise by this observation.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations